Measurement of active drag in swimming - Toussaint, H. M. (4th International Conference on Methods and Techniques in Behavioral Research, 27-30 August 2002, 2002)
A considerable part of the energy expended in swimming is used to overcome drag [1]. Drag is therefore one of the factors that may limit swimming performance. Throughout the history of swimming research, attempts have been made to measure this resistance.